Lokal Munchies / Nur Alya Afiqah Azmi - Azmi, Nur Alya Afiqah (2021)
This business project task is assigned to students to open their eyes and delve deeper into the field of business. Hence, applying business thinking among the new generation to empower the field as well as produce more entrepreneurs which generally business or entrepreneurship is a major and an important asset that able to cover the national economy. This report includes the introduction of the products being sold which is Lokal Munchies food brand, the project outcome and student’s experience in running the business throughout the allotted time. There are two editions with two types of Lokal Munchies products each were sold, and they are Cookies Edition and Cereal Edition. Cookies Edition involves chocolate chip cookies coated with melted chocolate of two flavours, hazelnut and mocha. The other edition is the Cereal Edition, which includes chocolate baby crunch and baby fruit loops poured with premium melted chocolate. In addition, the business project outcome of three weeks running business are included in this report, showing the sales made and the customers gained. Gains and losses from the business activity are also included in this part. In running business, there must be an experience gone through the activity of handling business. Experiences on how to manage the business, as well as handling the stocks, customer services, marketing and so forth are important for every entrepreneur to improve themselves in conducting business. This shows the journey and challenges faced throughout the course of this project. With the success of this project, it has given her the required level of confidence and communication skills as well as the knowledge and on how to run a business and to achieve a goal towards being a successful entrepreneur. Besides that, the entrepreneur also manages to build up her business network that will enable her to expand her business and branches that includes other related business. This project gives new perspectives to students and youth generations towards business which gives them chances and gain experience in running their own business as the main objective of this assignment is to involve them in business field. This could indirectly create more successful entrepreneurs for the future generations and helps in raising the national economy of Malaysia.